Primal cravings : your favorite foods made paleo - Keatley, Megan McCullough; Keatley, Brandon (Primal Blueprint Publishing, 2013)
"More than 125 recipes, each accompanied with a vibrant photo and detailed macronutrient calculations. Categorized by Breakfasts, Meat and main dishes, Sides and salads, Snacks and sweets, and the Basics, such as bread, sauces, and dressings, all recipes are no- or low-sugar, grain-free, gluten-free, dairy-optional, and embrace healthy primal/paleo good fats"--Page 4 of cover.